Simulation of hearing loss can induce pitch shifts for complex tones - Issei Ichimiya; Hiroko Ichimiya (PeerJ, 2023)
Background Most studies on pitch shift provoked by hearing loss have been conducted using pure tones. However, many sounds encountered in everyday life are harmonic complex tones. In the present study, psychoacoustic experiments using complex tones were performed on healthy participants, and the possible mechanisms that cause pitch shift due to hearing loss are discussed. Methods Two experiments were performed in this study. In experiment 1, two tones were presented, and the participants were asked to select the tone that was higher in pitch. Partials with frequencies less than 250, 500, 750, or 1,000 Hz were eliminated from the harmonic complex tones and used as test tones to simulate low-tone hearing loss. Each tone pair was constructed such that the tone with a lower fundamental frequency (F0) was higher in terms of the frequency of the lowest partial. Furthermore, partials whose frequencies were greater than 1,300 or 1,600 Hz were also eliminated from these test tones to simulate high-tone hearing loss or modified sounds that patients may hear in everyday life. When a tone with a lower F0 was perceived as higher in pitch, it was considered a pitch shift from the expected tone. In experiment 2, tonal sequences were constructed to create a passage of the song “Lightly Row.” Similar to experiment 1, partials of harmonic complex tones were eliminated from the tones. After listening to these tonal sequences, the participants were asked if the sequences sounded correct based on the melody or off-key. Results The results showed that pitch shifts and the melody sound off-key when lower partials are eliminated from complex tones, especially when a greater number of high-frequency components are eliminated. Conclusion Considering that these experiments were performed on healthy participants, the results suggest that the pitch shifts from the expected tone when patients with hearing loss hear certain complex tones, regardless of the underlying etiology of the hearing loss.